Fiscal Policy and Stock Market Efficiency in the Netherlands: An ARDL Bounds Testing Approach - Tsibikis, Konstantinos; Donders, Jan (Asian Journal of Empirical Research, 2020)
This paper aims to assess the effect of fiscal policy on the stock market efficiency in the Netherlands. This study is quantitative in where the data has been gathered from the World Data Bank and other databases. The variables included in the study are inflation, fiscal balance, industrial production index, stock prices/ returns and oil prices. In terms of the analysis, the Augmented Dickey-Fuller (ADF) has been used to determine the unit root. Moreover, the effect has been estimated through Bounds test. It has been determined from the analysis that interest rate, inflation, industrial production index and oil prices have a significant effect over the stock returns of the Netherlands. However, the Fiscal balance of GDP was determined to have insignificant influence over the stock returns of the Netherlands. The results of this study are restricted to the stock market of the Netherlands. With respect to the implications, there is a huge significance of these results as the stock returns of the Netherlands can increase while considering these factors.